2021
DOI: 10.3390/robotics10010049
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic and Friction Parameters of an Industrial Robot: Identification, Comparison and Repetitiveness Analysis

Abstract: This paper describes the results of dynamic tests performed to study the robustness of a dynamics model of an industrial manipulator. The tests show that the joint friction changes during the robot operation. The variation can be identified in a double exponential law and thus the variation can be predicted. The variation is due to the heat generated by the friction. A model is used to estimate the temperature and related friction variation. Experimental data collected on two robots EFORT ER3A-C60 are presente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Stribeck [10,11] found that many frictions have static properties, as shown in Figure 2. By summarizing the observed friction phenomena, the friction characteristics were described as Stribeck curves.…”
Section: Static Characteristics Of Frictionmentioning
confidence: 99%
“…Stribeck [10,11] found that many frictions have static properties, as shown in Figure 2. By summarizing the observed friction phenomena, the friction characteristics were described as Stribeck curves.…”
Section: Static Characteristics Of Frictionmentioning
confidence: 99%
“…In addition, it extends the Generalized Maxwell-Slip model to represent the observed friction phenomena at near-zero velocities. Hao [29] described the relationship between friction and temperature with a double exponential model and adjusted its parameters by genetic algorithms. However, separated identification of the friction model introduces extra outliers in the near-zero-velocity region, that will lead to bias in the dynamic model identification [11].…”
Section: Introductionmentioning
confidence: 99%
“…Trajectory control of industrial robots using multilayer neural networks driven by iterative learning control can be found in the paper (Chen and Wen, 2021). Dynamic and friction parameters of an industrial robot with repeatability identification, comparison and analysis are other important aspects of dynamic and robotic processes in the industry (Hao et al, 2021). The impact of gravity compensation on reinforcement learning in goalsetting tasks for robotic manipulators is a relatively new problem in dynamic disciplines (Fugal et al, 2021).…”
Section: Introductionmentioning
confidence: 99%